2012
DOI: 10.1103/physreva.86.062705
|View full text |Cite
|
Sign up to set email alerts
|

Universal three-body parameter in ultracold4He*

Abstract: We have analyzed our recently measured three-body loss rate coefficient for a Bose-Einstein condensate of spin-polarized metastable triplet 4 He atoms in terms of Efimov physics. The large value of the scattering length for these atoms, which provides access to the Efimov regime, arises from a nearby potential resonance. We find the loss coefficient to be consistent with the three-body parameter (3BP) found in alkali-metal experiments, where Feshbach resonances are used to tune the interaction. This provides e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
3
25
0
Order By: Relevance
“…See also the recent results for a − obtained for 39 K in Roy et al (2013). It is interesting to notice that for a < 0 the values for a − /r vdW are always between approximately −8 and −10.This observation led to the concept of a universal three-body parameter for atomic systems which has now been explored theoretically with several approaches (Chen, 2011;Naidon et al, 2012a;Wang et al, 2012a;Schmidt et al,2012;Sørensen et al,2012b;Naidon et al,2012b;Wang et al,2012).We note that the more recent experiment with metastable 4 He atoms (Knoop et al, 2012) has also shown results consistent with the universality of the three-body parameter. However, despite the fact that a + and a * ad derive from the same three-body parameter, they are not similarly universal, suggesting a breakdown in our understanding and thus posing an open question for both theory and experiment (Machtey et al, 2012a;Langmack et al, 2012).…”
Section: Experimental Observations In Ultracold Gasesmentioning
confidence: 78%
“…See also the recent results for a − obtained for 39 K in Roy et al (2013). It is interesting to notice that for a < 0 the values for a − /r vdW are always between approximately −8 and −10.This observation led to the concept of a universal three-body parameter for atomic systems which has now been explored theoretically with several approaches (Chen, 2011;Naidon et al, 2012a;Wang et al, 2012a;Schmidt et al,2012;Sørensen et al,2012b;Naidon et al,2012b;Wang et al,2012).We note that the more recent experiment with metastable 4 He atoms (Knoop et al, 2012) has also shown results consistent with the universality of the three-body parameter. However, despite the fact that a + and a * ad derive from the same three-body parameter, they are not similarly universal, suggesting a breakdown in our understanding and thus posing an open question for both theory and experiment (Machtey et al, 2012a;Langmack et al, 2012).…”
Section: Experimental Observations In Ultracold Gasesmentioning
confidence: 78%
“…When the three atoms enter the short-range region of the potential, they feel such a deep potential well that for all these species it would result in the same effect on the phase of the wavefunction, and lead to the same three-body parameter Λ. However, Efimov features for helium atoms, which interact through a shallow potential supporting only one two-body bound state, were shown to also follow the van der Waals universality, both theoretically [31] and experimentally [22].…”
Section: Introductionmentioning
confidence: 99%
“…For values of a beyond a c the transition probabilities T f i 2 in Eqs. (49), (72) and (81) become constant, therefore drastically changing the energy and scattering length dependence of the inelastic scattering rates [157]. In fact, in this unitarity regime (since T f i 2 approaches unit value), the rates become independent of a.…”
Section: Threshold Regime and Finite Energy Effectsmentioning
confidence: 99%